Ultimate load prediction of MMNCs structures. (15th September 2017) - Fuschi, P.; Pisano, A.A.
Abstract: The paper proposes a nonlocal limit analysis procedure to evaluate the load bearing capacity of metal matrix nanocomposites (MMNCs) structural elements. The promoted procedure rephrases and extends, in a nonlocal context, a static limit analysis numerical method, known in literature as elastic compensation method. Due to the ductility and the intrinsic nonlocal behaviour of MMNCs materials, a nonlocal elastic-perfectly plastic constitutive behaviour is hypothesized with the further hypothesis that nonlocality belongs only to the elastic phase. An associative von Mises type yield condition together with a nonlocal elasticity model of integral type are adopted. A nonlocal formulation of the finite element method is used throughout and a numerical application is presented and critically discussed with the aim to test the capability of the method in capturing the main features of the novel nonlocal limit analysis approach. Highlights: The paper proposes a novel nonlocal limit analysis procedure for metal matrix nanocomposites structures. The MMNCs are modelled as nonlocal elastic-perfectly plastic materials. A lower bound numerical procedure is extended by a nonlocal formulation of FEM. A von Mises yield condition is adopted with nonlocality confined to the elastic phase.